Characteristics of Pediatric Patient Transferred From Hospital-Based General Emergency Departments to Acute-Care Facilities: An Analysis of the Healthcare Cost and Utilization Project Nationwide Emergency Department Sample. Issue 7 (July 2020) - Barata, Isabel Araujo; Akerman, Meredith; Mahmooth, Zayan; Bradburn, Kathryn; D'Angelo, John
Abstract : Study Objective: The objective of this study was to analyze the characteristics of pediatric patients transferred from a hospital-based general emergency department (ED) to an acute care facility. Methods: Study data were abstracted from the 2010 Healthcare Cost and Utilization Project Nationwide Emergency Department Sample database. A multivariate logistic regression was constructed for pediatric patients (<18 years old) who require a transfer to an acute care facility from a general ED. Independent variables included in the model were age (<1, 1–4, 5–9, 10–14, 15–17 age in years), sex, insurance/payment method, and diseases/body systems using International Classification of Diseases, Ninth Revision, coding. Results: In the Healthcare Cost and Utilization Project/Nationwide Emergency Department Sample, 5.5 million ED visits were for children less than 18 years. About 1.5% of visits resulted in transfer. Children younger than 1 year had higher transfer rates as compared with 15 to 17 year old group (odds ratio [OR], 1.17; 95% confidence interval [CI], 1.089–1.146). Patients with Medicaid and self-pay compared with private insurance/health maintenance organization had 4% (OR, 0.96; 95% CI, 0.944–0.976) and 9% (OR, 0.91; 95% CI, 0.886–0.945), respectively, lower likelihood of being transferred. Patients with circulatory (OR, 8.43; 95% CI, 7.8–9.1), endocrine (OR, 5.9; 95% CI, 5.6–6.2), mental (OR, 5.44; 95% CI, 5.3–5.6), nervous system (OR, 5.2; 95% CI, 4.9–5.5), congenital anomalies (OR, 5.14; 95% CI, 4.5–5.9), hematology-oncology (OR, 4.49; 95% CI, 4.2–4.8), digestive, (OR, 1.52; 95% CI, 1.5–1.6), and other disorders (OR, 1.33; 95% CI, 1.3–1.4) had a higher odds of being transferred as compared with trauma/injury and poisoning, whereas patients with disorders related to genitourinary (OR, 0.96; 95% CI, 0.91–1.0), respiratory (OR, 0.79; 95% CI, 0.77–0.81), musculoskeletal (OR, 0.63; 95% CI, 0.58–0.68), skin (OR, 0.47; 95% CI, 0.45–0.50), infectious and parasitic (OR, 0.23; 95% CI, 0.22–0.25), and eyes/ears/nose/throat (OR, 0.09; 95% CI, 0.079–0.094) had a lower odds of being transferred as compared with trauma/injury and poisoning. Conclusions: Children younger than 1 year had relatively higher transfer rates. Patients covered by Medicaid and self-pay had the lowest likelihood of transfer. Transfer rates varied significantly by condition and the high-transfer diagnostic categories were related to circulatory, endocrine, nervous, hematology-oncology, and mental disorders as well as congenital anomalies, which may be related to a lack of ED or inpatient resources to care for children with problems that require more complex care.